2003
DOI: 10.1586/14760584.2.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of the Escherichia coli heat-labile enterotoxin as safe and strong adjuvants for intranasal delivery of vaccines

Abstract: Cholera toxin and Escherichia coli heat-labile enterotoxin are powerful mucosal adjuvants but their high toxicity hampers their use in humans. Site-directed mutagenesis has allowed the generation of several cholera toxin and E. coli heat-labile enterotoxin mutants with abolished or strongly reduced toxicity that still retain strong mucosal adjuvanticity. Among them, LTK63 (Ser to Lys substitution at position 63 in the A subunit) is completely nontoxic and LTR72 (Ala to Arg at position 72) retains a very low re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 27 publications
1
58
0
1
Order By: Relevance
“…8,9 Bacteria-derived particles may thus represent attractive alternatives to derivatives of toxins that are currently considered for use as mucosal adjuvants in humans. 10,11 The uptake of antigens through the nasal mucosa may be hampered by luminal drainage, especially when the vaccine is administered in a liquid form. 12 It has been shown, however, that the absorption of medications at this site can be improved by adding a composite thixotropic substance to render the formulation mucoadhesive.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Bacteria-derived particles may thus represent attractive alternatives to derivatives of toxins that are currently considered for use as mucosal adjuvants in humans. 10,11 The uptake of antigens through the nasal mucosa may be hampered by luminal drainage, especially when the vaccine is administered in a liquid form. 12 It has been shown, however, that the absorption of medications at this site can be improved by adding a composite thixotropic substance to render the formulation mucoadhesive.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of cAMP by LT is considered a dominant factor in mediating its adjuvant effects (6,7). However, studies in animal models using the partially active derivative, LTR72, and the enzymatically inactive mutant LTK63, have shown that these molecules retain at least some of the adjuvant properties of LT (8)(9)(10)(11)(12)(13)(14). These findings clearly indicate that the immunomodulatory properties associated with LT are not entirely dependent on ADP-ribosyltransferase activity.…”
mentioning
confidence: 99%
“…Besides stimulating the immune response directed against a coadministered Ag, LT is also highly immunogenic, eliciting strong humoral and cellular responses against itself (9). To circumvent the harmful drawbacks of the native LT toxin, several LT mutants with significantly reduced toxicity have been generated (10). LTK63 is an LT mutant with a serine-to-lysine substitution in position 63 of the A subunit, resulting in the complete loss of enzymatic activity (11).…”
mentioning
confidence: 99%